2020
DOI: 10.1038/s41392-020-0182-2
|View full text |Cite
|
Sign up to set email alerts
|

miR-410 induces both epithelial–mesenchymal transition and radioresistance through activation of the PI3K/mTOR pathway in non-small cell lung cancer

Abstract: Radiotherapy remains one of the major treatments for non-small cell lung cancer (NSCLC) patients; whereas intrinsic or acquired radioresistance limits its efficacy. Nevertheless, most studies so far have only focused on acquired resistance. The exact mechanisms of intrinsic radioresistance in NSCLC are still unclear. A few studies have suggested that epithelial-mesenchymal transition (EMT) is associated with radioresistance in NSCLC. However, little is known about whether the abnormal expression of specific mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 59 publications
0
48
0
Order By: Relevance
“…Increasing studies have revealed that miRNAs are closely associated with tumor cell proliferation, migration, invasion, drug resistance and apoptosis ( 6 , 7 ). For instance, miR-410 was revealed to promote epithelial-mesenchymal transition (EMT) and radio-resistance by targeting the PI3K/mTOR axis in NSCLC ( 8 ). miR-219 functioned as a tumor suppressor, which inhibited NSCLC and ovarian cancer cell growth and metastasis ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing studies have revealed that miRNAs are closely associated with tumor cell proliferation, migration, invasion, drug resistance and apoptosis ( 6 , 7 ). For instance, miR-410 was revealed to promote epithelial-mesenchymal transition (EMT) and radio-resistance by targeting the PI3K/mTOR axis in NSCLC ( 8 ). miR-219 functioned as a tumor suppressor, which inhibited NSCLC and ovarian cancer cell growth and metastasis ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…PTEN is an important tumor suppressor, and has been found to participate in the tumorigenesis and progression via downregulation of PI3-K/Akt pathway (18)(19)(20). PTEN was a vital regulator of cell reproduction, cell cycle, apoptosis and metastasis, and its low expression might cause tumor progression including OC (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…The EMT process not only leads to the invasion and migration of tumor cells, but also results in therapy resistance in cancer patients [58]. The overexpression of miR-410 enhances EMT and radiotherapy resistance by increasing DNA damage repair and regulates EMT through PTEN/PI3K/mTOR axis which leads to the radiotherapy resistance in non-small cell lung cancer (NSCLC) [59].…”
Section: Mirnas Regulate the Hallmarks Of Cancersmentioning
confidence: 99%